Palladium Dimer Supported on Mo2CO2(MXene) for Direct Methane to Methanol Conversion. Issue 2 (28th November 2018) - Sun, Xiang; Gao, Yijing; Zhao, Chenxia; Deng, Shengwei; Zhong, Xing; Zhuang, Guilin; Wei, Zhongzhe; Wang, Jian‐guo
Abstract: The direct conversion of methane to methanol remains a great challenge due to the difficulty of methane activation. Based on density functional theory calculations, the adsorption property and structure stability of supported Pd monomer and dimer are compared, and then Mo2 CO2 (MXene)‐supported Pd dimer is chosen as a catalyst to study the process of methane partial oxidation to methanol via oxygen dissociation, proton transfer, and hydrogen spillover reaction pathways, respectively. Calculation results show that, unlike Pd monomer, Pd dimer can provide the multiple adsorption sites for activation and adsorption of methane and oxygen, which is beneficial for the direct process of methane to methanol. Notably, the proton transfer pathway of undissociated oxygen with rate‐determining step of C–H bond dissociation can easily occur on Pd2 /Mo2 CO2 . And this process avoids the extra energy required for oxygen dissociation. Our calculations provide a new design strategy with supported Pd dimer catalyst for direct methane conversion into methanol. Abstract : Mo2 CO2 can serve as an ideal support to anchor Pd dimers . The proton transfer pathway of undissociated oxygen can easily occur on Pd2 /Mo2 CO2 . The proton transfer pathway avoids the extra energy required for oxygen dissociation. In future, a high reactivity catalyst for direct methane to methanol conversion can be designed by Palladium dimer supported on Mo2 CO2 with multiple adsorption sites.